2023
DOI: 10.1002/anie.202309472
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked Formation of Carbonate Radical Anions in the Oxidation of Iron(II) by Oxygen in the Presence of Bicarbonate

Abstract: Iron(II), (Fe(H2O)62+, (FeII) participates in many reactions of natural and biological importance. It is critically important to understand the rates and the mechanism of FeII oxidation by dissolved molecular oxygen, O2, under environmental conditions containing bicarbonate (HCO3−), which exists up to millimolar concentrations. In the absence and presence of HCO3−, the formation of reactive oxygen species (O2⋅−, H2O2, and HO⋅) in FeII oxidation by O2 has been suggested. In contrast, our study demonstrates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Previous studies have mentioned that high-valent metal species may play an important role in AOPs. [44][45][46] Recent studies have indicated that Cu(III) could exist under neutral and alkaline conditions and is considered the dominant oxidant in contaminant degradation. 47,48 Reports demonstrate that Cu(III) can be formed through several pathways (eqns ( 7)-( 9)).…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%
“…Previous studies have mentioned that high-valent metal species may play an important role in AOPs. [44][45][46] Recent studies have indicated that Cu(III) could exist under neutral and alkaline conditions and is considered the dominant oxidant in contaminant degradation. 47,48 Reports demonstrate that Cu(III) can be formed through several pathways (eqns ( 7)-( 9)).…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%
“…41,42 Moreover, recent studies indicate that carbonate radical ions may be of importance in aqueous Fe 2+ /O 2 systems (note, however, that the reactions studied in our experiments generally are at low pH, where the concentration of carbonate is neglectable). 43 The high-valent iron-mediated formation of C 1 and C 2 compounds from environmentally relevant substrates may involve three reaction types mediated by nonheme iron enzymes and relevant model systems, 44−46 outer-sphere electron transfer, C−H activation (hydrogen atom transfer, HAT�also known as hydrogen atom abstraction, HAA, or more generally as proton-coupled electron transfer, PCET), 39 or oxygen atom transfer (OAT). 31 The aim of the current project is to evaluate the scope of these reactions and, therefore, to test (i) whether all environmentally relevant C 1 and C 2 compounds in all possible oxidation states are available from the general model reaction described above and (ii) whether a major fraction of environmentally relevant organic matter in soil (proteins, carbohydrates, pectin, lignin, and humic substances) are (partially) degrading in similar pathways.…”
Section: ■ Introductionmentioning
confidence: 99%